2017
DOI: 10.1016/j.poly.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene-containing β-diketonate complex of copper(II): X-ray crystal structure and electropolymerization

Abstract: International audienceIn this work, we report the synthesis of the asymmetrical β-diketone 1-(thiophen-2-yl)-3-(thiophen-3-yl)propane-1,3-dione (HL) and its corresponding bis(β-diketonate)copper(II) complex [Cu₁-(thiophen-2-yl)-3-(thiophen-3-yl)-1,3-propanedionate₂] (CuL2), isolated in 60 and 86% yields, respectively. These two new compounds have been characterized by elemental analysis, FT-IR and UV–Vis spectroscopy and, in the case of HL, by 1H and 13C NMR spectroscopy. Additionally, both compounds were auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The 2-thienyl rings are strongly disordered thus precluding any further discussion of their metrical parameters. We previously observed such a disorder, albeit much weaker, in structures of thiophen-containing compounds solved at low temperature [18][19][20]. All close intermolecular contacts correspond to van der Waals interactions.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The 2-thienyl rings are strongly disordered thus precluding any further discussion of their metrical parameters. We previously observed such a disorder, albeit much weaker, in structures of thiophen-containing compounds solved at low temperature [18][19][20]. All close intermolecular contacts correspond to van der Waals interactions.…”
mentioning
confidence: 84%
“…synthesized by us. 18,29,30 In any case, it should be noted that both deposits have a fully reversible charge response, as is the case with the other thiophene derivatives studied, they have been proposed to be tested as battery cathodes. 30,31 These results, which do not seem very auspicious in that sense, will allow to propose structural modifications in search of the preparation of metal containing polymers.…”
Section: Electrochemical Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…This lack of massive deposit of polymer could be attributed to either the weak contribution of the 2-thienyl group to the spin density or to the electron-attracting effect of the CF 3 moieties that limits the extension of the electropolimerization and does only allow the formation of soluble short oligomers with low molecular weight. Very recently, we have shown that when the CF 3 substituent is absent in the thienyl-containing β-diketonate structure, polymeric massive deposits can be obtained on the electrode surface [55]. …”
Section: Electrochemical Studymentioning
confidence: 99%
“…Recently, the synthesis, characterization and antifungal activities, together with crystal structure determinations, of thiophene-based heterocyclic chalcones have been investigated (Ming et al, 2017). Thiophene-containing -diketonate complexes of copper(II) have been studied and their deposits obtained by electropolymerization have been characterized (Oyarce et al, 2017). Combinations of the thiophene ring with other heterocyclic rings have also been investigated, such as a -keto-enol group embedded with thiophene and pyridine moieties giving interesting applications in the field of solidphase extraction (Radi et al, 2016).…”
Section: Chemical Contextmentioning
confidence: 99%